Validation of the EQ-5D in Taiwan using item response theory - Tzu-Hung Liu; Andrew D. Ho; Yu-Tien Hsu; Chih-Cheng Hsu (BMC, 2021)
Abstract Background Our study aims to provide validity evidence for the EuroQol five dimensions questionnaire (EQ-5D) in the National Health Interview Survey of Taiwan in the 2013 wave and further interpret the EQ-5D scores for patients with chronic diseases. Another goal of the study was to use item response theory (IRT) to identify items that are informative for assessing quality of life using EQ-5D. Methods There were 17,260 participants, aged 12-64, who completed the interviews in our study. Psychometric methods, including factor analysis and the IRT model known as the Graded Response Model (GRM), were used to assess the unidimensionality of EQ-5D and its item properties. Correlation analysis was used to assess whether EQ-5D scores are associated with scores from the 36-Item Short Form Survey (SF-36). Results The EQ-5D scores have moderate internal consistency (Cronbach's alpha: 0.60) and a scree plot suggests that the EQ-5D measure is unidimensional. The item information function analysis from the IRT model demonstrates that the first 3 items, "mobility," "self-care," and "usual activities" are the most informative items for patients who have chronic diseases and health-related quality of life below the 10th percentile. The EQ-5D scores have a moderate correlation (r: 0.61) with SF-36 scores. Conclusions The EQ-5D scale shows promise for use in the general population. The IRT model informs our interpretation of the EQ-5D scores. Given the time constraints in clinical settings, we suggest using the first three items in EQ-5D to measure the health-related quality of life for patients with chronic diseases.